2013
DOI: 10.1371/journal.pone.0071965
|View full text |Cite
|
Sign up to set email alerts
|

A Cell System for Phenotypic Screening of Modifiers of SMN2 Gene Expression and Function

Abstract: Spinal muscular atrophy (SMA) is an inherited neurodegenerative disease caused by homozygous inactivation of the SMN1 gene and reduced levels of the survival motor neuron (SMN) protein. Since higher copy numbers of the nearly identical SMN2 gene reduce disease severity, to date most efforts to develop a therapy for SMA have focused on enhancing SMN expression. Identification of alternative therapeutic approaches has partly been hindered by limited knowledge of potential targets and the lack of cell-based scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Classically, SMA is regarded as a motor neuronal disease, but recent animal and hybrid models have indicated that the earliest morphological defects occur at the NMJ (32,33), indicating SMA is an NMJ disease. Because a human model to study NMJ function is lacking, we knocked down SMN mRNA by shRNA in 201B7 MYOD (201B7 MYOD -SMN KD ) to study the molecular pathology of SMA on an isogenic background (34,35). 201B7 MYOD -SMN KD iPSCs showed a significant decrease in mRNA level and a 60% decrease in SMN protein expression (Supplemental Figure 10, F and G).…”
Section: Resultsmentioning
confidence: 99%
“…Classically, SMA is regarded as a motor neuronal disease, but recent animal and hybrid models have indicated that the earliest morphological defects occur at the NMJ (32,33), indicating SMA is an NMJ disease. Because a human model to study NMJ function is lacking, we knocked down SMN mRNA by shRNA in 201B7 MYOD (201B7 MYOD -SMN KD ) to study the molecular pathology of SMA on an isogenic background (34,35). 201B7 MYOD -SMN KD iPSCs showed a significant decrease in mRNA level and a 60% decrease in SMN protein expression (Supplemental Figure 10, F and G).…”
Section: Resultsmentioning
confidence: 99%
“…For spliceosomal snRNA analysis, snRNA-specific reverse primers were used in the RT reaction according to a previous study ( 51 ). All primers and probes used in RT-qPCR and northern blot experiments were previously described ( 28 30 , 53 , 54 ).…”
Section: Methodsmentioning
confidence: 99%
“…SMN depletion induces cell proliferation defects in NIH3T3 cells (Li et al, 2013; Lotti et al, 2012). We found that these defects are associated with a decrease in the proportion of cells in S phase and a corresponding increase of those in G1 (Figure S2A), akin to the effects of U7 snRNP inhibition on the cell cycle (Wagner and Marzluff, 2006).…”
Section: Resultsmentioning
confidence: 99%